A combined biological and clinical rationale for evaluating metastasis directed therapy in the management of oligometastatic prostate cancer. (November 2020) - Kucharczyk, Michael J; So, Jonathan; Gravis, Gwenaelle; Sweeney, Christopher; Saad, Fred; Niazi, Tamim
Graphical abstract: Highlights: RCTs have suggested that a lower metastatic volume may predict for benefit with local therapies. Molecular evidence has signaled that less aggressive disease biology predicts for MDT's benefit. Genomic instability is a predominant driver of MPC's biological aggressiveness. Clinical equipoise has not yet been overcome for introducing MDT as a standard of care. MPC RCT patient selection should model disease activity as a composite of biology and volumeollows. Abstract: The initial management of potentially oligometastatic hormone sensitive prostate cancer has been complicated by rapid advances in the field. Clinically, subgroup analyses of two randomized control trials have suggested that a specific synchronous oligometastatic prostate cancer state may be predictive for benefit from radiation to the primary. Further exploration of metastasis-directed therapy has been supported for various prostate cancer populations among three phase II clinical trials. There are numerous caveats in applying this evidence, a dilemma being addressed by present and upcoming clinical trials. Despite existing clinical equipoise and an avenue to address this uncertainty, the temptation to combine this evidence off-trial exists. Matters have become more complex as our ability to evaluate metastatic disease and tumour biology have also matured. This paper synthesizes our understanding of prostate cancer's natural history into a model which rationalizes both the theoretical benefits and limitations of metastasis directed therapy. We postulate that a metastatic prostate cancer's total disease activity is primarily driven by the combination of its burden of disease and underlying biology, namely genomic instability, then highlight the numerous remaining questions that challenge this hypothesis. This review focuses on harmonizing the language used to describe the disease, the current efforts exploring this hypothesis, and the need for clinical trial participation to appropriately advance patient care.